Performance Evaluation of IARI Wheat Seed-cum-Fertilizer Plot Drill for Pearl Millet-Wheat Cropping System on Permanent Raised Bed System - Sawant, Chetan Kumar P.; Kumar, Adarsh; Mani, Indra; Singh, J. K.; Yadav, Rajbir; Sahoo, R. N. (Journal of Agricultural Engineering, 2019)
A four-row IARI seed-cum-fertilizer plot drill developed at ICAR-IARI, New Delhi for permanent raised bed system was evaluated under pearl millet-wheat cropping system. The machine was fitted with two Oyjord metering mechanisms with four outlets for metering seed and fertilizer. Successful seeding on raised beds with pearl millet crop residue was achieved by first cutting the plant residue with a plain disc coulter, followed by seed drilling in narrow slit furrows opened by double disk furrow openers. The plot drill required 33.56 kW tractor for its operation in sandy loam soils, and two operators to feed measured quantity of seed and fertilizer. Field capacity of the plot drill was 0.17 ha.h-1 at 1.5 km.h-1 forward speed of operation. Field machine index, field efficiency and cost of operation were 72.72, 80 % and ` 648/- per hour, respectively. The plant stands of wheat sown on permanent raised beds with the developed plot drill were significantly higher than with precision plot drill.